Friction-induced vibrations and self-organization : mechanics and non-equilibrium thermodynamics of sliding contact - Nosonovsky, Michael, author; Mortazavi, Vahid (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"Friction induced instabilities can lead to vibrations, which are often undesirable (e.g., car brake squeal). On the other hand, they may be useful (e.g., music sound generation). New materials capable to resist wear and heal minor damage (self-healing) in themselves can be developed if the ability for self-organization is embedded into the material. This book emphasizes thermodynamic analysis of friction-induced instabilities, vibrations, and self-organization as well as fundamental properties of friction and wear related to these"--provided by publisher